2019
DOI: 10.1016/j.apmr.2018.12.024
|View full text |Cite
|
Sign up to set email alerts
|

Nonlinguistic Cognitive Factors Predict Treatment-Induced Recovery in Chronic Poststroke Aphasia

Abstract: Objective: To determine if pre-treatment non-linguistic cognition predicted language treatment outcomes and if so, which specific non-linguistic cognitive subskills predicted naming therapy outcomes. Design: Retrospective Setting: Research clinic Participants: Study 1 included data from 67 persons with aphasia who underwent language treatment and a pre-treatment cognitive-linguistic assessment battery. Study 2 included data from 27 Study 1 participants who completed additional pre-treatment non-linguistic cogn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
45
3

Year Published

2020
2020
2025
2025

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 66 publications
(54 citation statements)
references
References 24 publications
6
45
3
Order By: Relevance
“…Dorsolateral aspects of SFG have been implicated in attention and working memory (Li et al, 2013), suggesting that individuals with aphasia may have recruited left SFG during language processing to maintain information in short-term memory (e.g., retrieving the name of the picture while reading the written phrase during semantic feature judgment). This finding is in line with work in the field of aphasia emphasizing the role of non-linguistic cognition in language functions (Wright and Shisler, 2005;Villard and Kiran, 2017;Gilmore et al, 2019). Individuals with aphasia also demonstrated engagement of LSMG during semantic feature and RPCG during picture naming, which were not significantly engaged by the healthy groups for the real picture condition and may represent recruitment of domain-general cognitive regions when processing language in the context of aphasia (i.e., engaged when task complexity increases, irrespective of modality; Fedorenko et al, 2013).…”
Section: Activation Patterns In Individuals Withsupporting
confidence: 89%
“…Dorsolateral aspects of SFG have been implicated in attention and working memory (Li et al, 2013), suggesting that individuals with aphasia may have recruited left SFG during language processing to maintain information in short-term memory (e.g., retrieving the name of the picture while reading the written phrase during semantic feature judgment). This finding is in line with work in the field of aphasia emphasizing the role of non-linguistic cognition in language functions (Wright and Shisler, 2005;Villard and Kiran, 2017;Gilmore et al, 2019). Individuals with aphasia also demonstrated engagement of LSMG during semantic feature and RPCG during picture naming, which were not significantly engaged by the healthy groups for the real picture condition and may represent recruitment of domain-general cognitive regions when processing language in the context of aphasia (i.e., engaged when task complexity increases, irrespective of modality; Fedorenko et al, 2013).…”
Section: Activation Patterns In Individuals Withsupporting
confidence: 89%
“…For example, Dignam et al 52 revealed that cognitive factors such as verbal working memory predict SLT-related improvements in naming. Similarly, a study by Gilmore et al 53 suggested that cognitive factors predict the outcome of SLT targeting either sentence comprehension or naming in aphasia. Much like Breitenstein et al, 18 Nouwens et al, 29 and Godecke et al, 30 these preliminary data from POLAR suggest participants with more severe aphasia are less likely to respond to SLT.…”
Section: Predicting the Outcome Of Behavioral Therapy Of Aphasiamentioning
confidence: 96%
“…5 The prediction of aphasia recovery has largely focused on left hemisphere lesion-related factors, including lesion size and location 6 and pretreatment cognitive skills. 7 However, the integrity of the brain tissue spared by the stroke may contribute to neural plasticity and influence treatment response independently of left hemisphere damage. 8 White matter hyperintensities (WMH) of presumed vascular origin is a relevant radiological marker of brain health.…”
Section: Introductionmentioning
confidence: 99%